Effects of an Alleyway Brush on the Behavior of Commercial Beef Heifers and Cows During a 7-day CO-Synch + CIDR Protocol and Pregnancy Outcomes - Danielle M. Ellinghuysen (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective of this study was to explore the effects of using a cattle brush device as positive reinforcement during the handling events of the estrus synchronization (ES) protocol on temperament and pregnancy rates of beef cows and heifers. Study Description: A total of 71 heifers and 162 cows at the Agricultural Research Center, Hays, KS, were stratified by reproductive/physiological status and randomly assigned to treatment (TRT) or control (CTRL). During the ES protocol, TRT animals encountered a spring-mounted brush before entering the chute, while CTRL animals did not. Chute score (CS) and exit velocity (EV) were recorded on each day. Estrotect indicators were applied and measured. Pregnancy was diagnosed by ultrasound 33 days post-timed artificial insemination (TAI) for heifers and 68 days for cows. The Bottom Line: Bovine temperament can be improved through sequential handling events, but additional research is needed to determine the effects of positive reinforcement with a brush in the chute alley on reproductive production measures.
Keywords: temperament; positive reinforcement; estrus synchronization